Application of the AHP-TOPSIS Method to Determine the Feasibility of Fund Loans - Juniar - Hutagalung (Jurnal Pekommas, 2021)
This study aims to produce a decision support system (DSS) for the feasibility of providing loan funds as a tool and recommendation for cooperatives with several criteria as the basis for decision making, namely: business ownership status, ability, character, collateral, income, and salary. The system implementation uses the Visual Studio 2010 and Microsoft Access 2010 programming languages. This application is designed for effective and efficient decision-making. This program uses two methods, namely AHP, to determine the weight of the criteria and TOPSIS for determining to rank. This combination is designed for high-accuracy applications. The results of the pairwise comparison matrix calculation show that the weights obtained are acceptable and consistent. This application generates alternative customer data from the highest preference value (feasible to get a loan) to the lowest (not feasible).